Fabrication and characterization of polymeric based asymmetric ultrafiltration membrane for lysozyme separation towards biotechnology development - Sofiah Hamzah (Fakulti Sains dan Teknologi, 2011)
This study is aimed to develop an optimum asymmetric ultrafiltration membrane for protein lysozyme separation. The effects of polymer concentration and post treatment medium on membrane performance and morphology have studied.